Asian decent work decade resource kit : competitiveness, productivity and jobs. (International Labour Organization, 2008)
Offers a brief introduction to ILO's knowledge base on Asia and the Pacific. The resource kit can be useful to people who have a general interest in the issues as well as specialists who need additional technical resources.